2020
DOI: 10.1021/jacs.0c04675
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Nitrone-Conjugated Secondary Metabolite Targeting the Ribosome

Abstract: Many microorganisms possess the capacity for producing multiple antibiotic secondary metabolites. In a few notable cases, combinations of secondary metabolites produced by the same organism are used in important combination therapies for treatment of drug-resistant bacterial infections. However, examples of conjoined roles of bioactive metabolites produced by the same organism remain uncommon. During our genetic functional analysis of oxidase-encoding genes in the everninomicin producer Micromonospora carbonac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 32 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…In vitro translation assay showed that, for E. coli ribosome with A2059G mutation which causes resistance to macrolides, the IC 50 values of rosamicin, everninomicin H (an analog of everninomicin F) and everninomicin P were >100, 0.1, and 0.1 μM, respectively. For E. coli ribosome with A2471C mutation which causes resistance to everninomicins, the IC 50 values of everninomicin H, rosamicin, and everninomicin P were >50, 5, and 10 μM, respectively 66 …”
Section: Challenges and Advances In Ribosomal Antibiotics And Bacterial Ribosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro translation assay showed that, for E. coli ribosome with A2059G mutation which causes resistance to macrolides, the IC 50 values of rosamicin, everninomicin H (an analog of everninomicin F) and everninomicin P were >100, 0.1, and 0.1 μM, respectively. For E. coli ribosome with A2471C mutation which causes resistance to everninomicins, the IC 50 values of everninomicin H, rosamicin, and everninomicin P were >50, 5, and 10 μM, respectively 66 …”
Section: Challenges and Advances In Ribosomal Antibiotics And Bacterial Ribosomesmentioning
confidence: 99%
“…A study showed that for S. aureus with G2576T mutations, the MIC range of linezolid was 16–32 μg/ml, while that of tedizolid was 1–2 μg/ml 65 . Limbrick et al 66 identified a nitrone‐conjugated secondary metabolite everninomicin P from mutated Micromonospora carbonacea var. aurantiaca 66 .…”
Section: Challenges and Advances In Ribosomal Antibiotics And Bacterial Ribosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally acknowledged that the rarely observed orthoester linkage is necessary for the antibiotic properties of the orthosomycins. Although the orthosomycin family includes hygromycin B, everninomicin, avilamycin, flambamycin, curamycin, etc., the former three members have been extensively studied, especially in the aspect of their bioactivity and biosynthesis [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Herein, restricted by the space, everninomicin (EVN) and avilamycin (AVI) will be mainly discussed in this review.…”
Section: Orthosomycinsmentioning
confidence: 99%
“…Until now, twenty EVN ( 43 – 62 ) ( Figure 8 ) have been purified from wide- or mutant-type M. carbonacea var. africana [ 59 , 60 , 61 , 62 , 63 , 71 ], while thirty-seven AVI ( 63 – 99 ) ( Figure 9 ) have been isolated from the wide- or mutant-type Streptomyces viridochromogenes Tü57 [ 59 , 64 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Structurally, EVN and AVI share the same seven-sugar core (rings B to H) and characteristic substituted partner including two orthoester linkages located between rings C and D and rings G and H and a methylenedioxy bridge attached to ring H. The major differences between EVN and AVI are attributed to the presence (or absence) of the A-ring nitrosugar and the orsellinic acid in EVN (or in AVI).…”
Section: Orthosomycinsmentioning
confidence: 99%